Bending Back to the Professional Activities: Unveiling the Role of Reflective Practice in Teachers’ Professional Development - Rauteda, Khem Raj (Journal of NELTA Gandaki, 2024)
Reflection and reflective practices are important to develop professionalism. The importance of those practices has been highly emphasised in teaching, learning, and teachers’ professional development. With this backdrop, the study aims to investigate the English teachers’ reflective practices and examine their role in their professional development. I used narrative inquiry as a research design where the sample was selected using purposive sampling. An in-depth interview was used as a research tool to collect information and the interviews were conducted using interview guidelines. The collected data was recorded, transcribed, coded, categorised, and thematically analyzed. The study found that the English language teachers used action research, case studies, diary writing, reflective journals, and students’ feedback as reflective practices. Moreover, the study has uncovered that reflective practices are important for teachers to have self-analysis, find strengths and weaknesses of the learners and self, plan, act, and further plan the lesson, empower the learners, solve critical incidents, to have the active engagement of learners in teaching-learning activities, and to grow as a professional person. The study implies that every teacher should have a reflection on their practices for the betterment of teaching, learning, and growing professionally.